The Factors that Affect the Working Capital Policy of Manufacturing Companies that Go Public in Indonesia - Samsuddin Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was to determine and analyze the factors that affect Working Capital Policy on Manufacturing Companies Go Public in Indonesia and also to determine the most dominant factor affecting Working Capital Policy. The population of research is Manufacturing Companies listed in Indonesia stock Exchange year 2018-2020. Sample selection is done by the company that the criteria contained in The Compass 2018-2020 and from 156 Companies Manufacturing Go Public in Indonesia obtained a sample of the company amounted to 22 companies with 3 years of observation, so that the number of observations is 66. The Data used is secondary data. Source of data derived from the site www.idx.co.id. The method of collecting data is through the method of documentation and literature study method. Methods of data analysis is using multiple linear regression after fulfilling the terms of the classical assumption test. The results showed that the partial profit margin significantly affect the cash as a component of Working Capital Policy, while tangibility, sale growths, cash flow volatility, and real gdp growth has no significant effect on cash, inventory, receivables as a component of Working Capital Policy. Simultaneously tangibility, profit margin, sale growth, cash flow volatility, and real gdp growth significantly influence the cash as a component of Working Capital Policy.